A social community caregiving approach towards gender-based violence and femicide : the role of men in Thembisa Uniting Reformed Church - Setoto, Godisamang Isar (Stellenbosch : Stellenbosch University, 2026)
Thesis (MTh)--Stellenbosch University, 2026.